2016
DOI: 10.1186/s12966-016-0375-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physical activity during transition to retirement: a cohort study

Abstract: BackgroundRetirement is a major life transition which may affect lifestyle. The aim of this study is to examine within-individual changes in physical activity during the transition from full-time work to retirement.MethodsThe study population consisted of 9,488 Finnish public-sector employees who retired in 2000–2011 and who reported their leisure-time and commuting physical activity before and after retirement. On average, participants provided data at 3.6 (of the four) repeat examinations during 10 years bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
95
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 25 publications
14
95
1
1
Order By: Relevance
“…This study showed that in early old age, an important time of transition between work and retirement when behavior change may be possible,57 higher PAEE and greater time spent in LPA and MVPA and less sedentary time were related to more favorable CVD biomarker profiles. The associations found were stronger in women than men and remained after adjustment for covariates.…”
Section: Discussionmentioning
confidence: 62%
“…This study showed that in early old age, an important time of transition between work and retirement when behavior change may be possible,57 higher PAEE and greater time spent in LPA and MVPA and less sedentary time were related to more favorable CVD biomarker profiles. The associations found were stronger in women than men and remained after adjustment for covariates.…”
Section: Discussionmentioning
confidence: 62%
“…These were therefore treated as covariates. We obtained information from the employers' registers regarding participants' sex, age at retirement and occupational status categorized according to the Classification of Occupations by Statistics Finland 22, as in previous studies 23, 24, into three groups: ‘high’, including physicians and teachers; ‘intermediate’, including registered nurses and technicians; and ‘low’, including maintenance workers and cleaners. Level of education (high = university degree; intermediate = high school or vocational school; low = basic education) was obtained from Statistics Finland 25, while marital status (married/cohabiting; single; divorced/widowed), smoking (current smoker versus not), depression (‘Have you ever been diagnosed with depression?’ yes versus no) and self‐reported health (poor versus good) were elicited by the questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 The time spent on activity at each intensity level in hours per week was multiplied by the average energy expenditure of each activity, expressed in metabolic equivalent (MET). Physical activity was categorized into four groups:…”
Section: Assessment Of Covariatesmentioning
confidence: 99%